Поэтика карнавализации в романной прозе Ж. Жене - Ващенко, Ю.А.; Семенец, О.С. (Харкiвський нацiональний унiверситет iм. В.Н. Каразiна, 2012)
В статье анализируется функционирование элементов карнавальной парадигмы (хронотоп, карнавальне мезальянсы и профанации, гротескный образ тела, поэтика увенчаний-развенчаний) в романах Ж. Жене «Богоматерь цветов», «Чудо о розе», «Торжество похорон», «Кэрель из «Бреста» и «Дневник вора» в контексте художественного целого. Результаты исследования расширяют представление о жанровых и поэтикальных доминантах романов и позволяют расставить существенные акценты в трактовке этико-эстетической концепции, сформированой в романной прозе Ж. Жене. The article deals with analysis of functioning of elements of carnivalesque paradigm (chronotope, carnivalesque misalliances and profanities, grotesque image of the body, poetics of crownings-discrownings) in Jean Genet’s novels “Our Lady of the Flowers”, “The Miracle of the Rose”, “Funeral Rites”, “Querelle of Brest” and “The Thief's Journal” in the context of an artistic whole. The results of the investigation extend the notion of novels poetical dominants and allows to place significant emphasis in the interpretation of ethical and aesthetic concept, formed in Jean Genet’s novelistic prose.
Ващенко Юлія Анатоліївна, к. філол. н., доцент кафедри історії зарубіжної літератури та класичної філології ХНУ імені В. Н. Каразіна. Семенець Ольга Сергіївна, викладач кафедри латинської мови і медичної термінології Харківського національного медичного університету.
Keywords: Жене Ж.; роман; маргинальное сознание; карнавализация; хронотоп; театрализация; Jean Genet; novel; marginal consciousness; chronotope; staging